ABDULLA ORIPOV SHE’RLARIDA TABIAT TASVIRI (Archive of Conferences, 2021)
This article analyzes the artistic aspects of the depiction of nature in the poems of the People's Poet of Uzbekistan Abdulla Aripov. Conclusions are made about the secrets of the harmony of image and poetic content